(untitled) (Dhaka University Journal of Science, 2017)
This paper describes the design, development and performance of a locally developed data acquisition system for solar PV module with variable load. The system can automatically change the operating point of a PV module and acquire the output voltage and load current into computer and then analyze. To change the operating point, a variable load has been developed by IRF250 MOSFETs. The current drawn by the load from the PV module is controlled by a staircase voltage, which is developed by a counter and a DAC. The count value of the counter and hence the voltage level of the staircase is changed by an Arduino-based controlling unit. To get the short-circuit current, the PV module is connected in series with a high ampere power supply and the voltage across the PV module is conditioned by a difference amplifier and fed to an ADC channel of the controlling unit. The output current of the PV module has been sensed by a Hall sensor, ACS712, and read by another ADC channel. To make the whole system automatic, a program has been developed using Arduino IDE and loaded in the Arduino board. With the help of this program, the system can measure the current and voltage of the PV module and send to a PC. This acquired data is processed by software and the performance of the PV module is obtained. The system has been developed in laboratory and its performance has been studied. Although, there are some fluctuations in the acquired data but with filtration satisfactory performance is obtained. This instrument can be used for PV module testing purpose. Dhaka Univ. J. Sci. 65(1): 67-72, 2017 (January)